Sterilization of propylene/ethylene random copolymers: Annealing effects on crystalline structure and transparency as influenced by polymer structure and nucleation (eXPRESS Polymer Letters)
An extensive investigation of three different series of isotactic ethylene/propylene (EP) random copolymers was performed to understand the factors influencing the change in optical properties in the steam sterilization of extrusion cast films from such materials. Different analytical methods (differential scanning calorimetry (DSC), X-ray diffraction and electron microscopy) were employed to elucidate structural changes determining film optics, and in addition to the polymer structure parameters also nucleation and processing effects were studied. The findings clearly show that a combination of homogeneously randomized comonomer distribution and nucleation can partly inhibit lamellar thickening in sterilization, thus preserving high transparency even after a heat treatment. In detail, attention has to be paid to the combined effects of primary and secondary post-crystallization, which both are affected by the chain regularity.